2017
DOI: 10.1620/tjem.242.241
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum 25(OH)D<sub>3</sub> Levels in Post-Menopausal Japanese Women with Osteoporosis after 3-Year Bisphosphonate Treatment

Abstract: Osteoporosis is characterized by the systemic impairment of bone mass, strength, and microarchitecture, leading to an increased risk of fragility fracture. Bisphosphonates (BPs) are the first-line drugs for osteoporosis. Vitamin D is considered to be essential for osteoporotic treatment. However, long-term effects of BPs on the serum levels of 25-hydroxyvitamin D 3 (25(OH)D 3 ) are unknown. Accordingly, in this retrospective study, we collected clinical data of 41 post-menopausal Japanese women with osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…The lack of serum 25(OH)D 3 data is a major limitation of this study. We have previously reported that 4 months of BP therapy significantly decreased 25(OH)D 3 and that 3-year BP therapy without vitamin D supplementation significantly increased 25(OH)D 3 [15, 16]. However, in our patient’s case, BMD rapidly increased; thus, we speculated that 25(OH)D 3 levels might not have had an obvious influence on the results in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…The lack of serum 25(OH)D 3 data is a major limitation of this study. We have previously reported that 4 months of BP therapy significantly decreased 25(OH)D 3 and that 3-year BP therapy without vitamin D supplementation significantly increased 25(OH)D 3 [15, 16]. However, in our patient’s case, BMD rapidly increased; thus, we speculated that 25(OH)D 3 levels might not have had an obvious influence on the results in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…As adequate levels of serum 25(OH)D 3 are important in osteoporotic treatment, the lack of the data on serum 25(OH)D 3 is another major shortcoming of this study. However, we recently observed that 3-year BP therapy without vitamin D supplementation significantly increased serum 25(OH)D 3 [19]. Although not measured in this study, we presumed that serum 25(OH)D 3 levels were sufficient in our patients owing to their prior long-term BP therapy.…”
Section: Discussionmentioning
confidence: 70%
“…It was noteworthy that all of the OP patients in those studies had taken vitamin D supplementation 1922. We previously found that serum 25(OH)D levels were significantly increased after 3-year BP therapy without additional vitamin D in Japanese postmenopausal OP patients 23. On the other hand, serum 25(OH) D had decreased significantly after 4 months of BPs in a Japanese postmenopausal OP cohort 24.…”
Section: Discussionmentioning
confidence: 98%